Problematic Social Media Usage and Anxiety Among University Students During the COVID-19 Pandemic: The Mediating Role of Psychological Capital and the Moderating Role of Academic Burnout - Jiang, Yan (Frontiers in Psychology, 2021)
The outbreak of COVID-19 has greatly impacted university students’ studies and life. The objective of this study was to examine a possible mediating role of psychological capital and moderating role of academic burnout in the relationship between mobile social media usage and anxiety among university students during COVID-19. A total of 3,123 undergraduates from universities in Shanghai participated in an online survey,from March to April 2020. The results showed that mobile social media usage among university students predicted their levels of anxiety. A mediation analysis indicated that psychological capital mediated the relationship between mobile social media usage and anxiety. Furthermore, for university students whose academic status had been affected by the COVID-19 pandemic, the effects of both mobile social media usage and the psychological capital on anxiety were moderated by academic burnout. For university students whose academic status was not affected by the COVID-19 pandemic, academic burnout moderated the effects of psychological capital but not the effects of social media usage on anxiety. The results highlighted the underlying mechanisms in the relationship between mobile social media usage and anxiety. These findings provide practical insights into the development and implementation of psychological interventions when facing an pandemic.